PATHOMORPHOLOGICAL CHARACTERISTICS OF SALIVARY GLAND TUMORS AMONG THE POPULATION OF KHOREZM REGION - Sultanov B. B; Karimov R. Kh; Babajanov A. M (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: Salivary diseases of the gland develop a heterogeneous pathological range of inflammatory, benign, and malignant diseases and require accurate diagnostic assessment and informed management, with this work aimed to assess reliable FNAC as well as identify the pitfalls, and determine how the informed use of morphological, molecular, and statistical analysis would benefit in characterizing salivary gland lesions on a specific population. Method: Advances in fine needle aspiration cytology (FNAC), histopathology, immunohistochemistry (IHC), and molecular profiling have refined classification, especially in the revised World Health Organization (WHO) system that has introduced genetic characterization, and through the synergistic representation of FNAC, histopathology, IHC, and microstructural analyses with powerful patterns of statistics, the study applies a multi-faceted method that deals with the reliability of diagnosis and the characterization of lesions in the population-based scenario. Result: The outcome was that FNAC had very high sensitivity and specificity rates in the majority of lesions with certain pitfalls being cystic portions of tumors, but the molecular profiling increased classification and prognostic performance, which enhanced morphological and cytological data. Novelty: These results contribute to the importance of FNAC combined with molecular and histopathological analysis to reduce potential diagnostic errors, improve clinical description of the WHO-based disease categories, and outline specific management procedures, paving the way to future population-oriented studies of the molecular phenotypes of oral pathology.